2011
DOI: 10.1002/ajh.22189
|View full text |Cite
|
Sign up to set email alerts
|

Intensive short‐term chemotherapy regimen induces high remission rate (over 90%) and event‐free survival both in children and adult patients with advanced sporadic Burkitt lymphoma/leukemia

Abstract: The optimal treatment of advanced sporadic Burkitt lymphoma in adults is still a matter of debate. The salutary results of pediatric therapies did open the road for improving the adult outcome. Between May 1988 and March 2009, 71 consecutive patients-46 adults, 25 children-affected by Burkitt lymphoma/leukemia were treated with the same intensive pediatric protocol alternating vincristine, adriamycine and fractionated ciclophosphamide (phase A) with high dose methotrexate and high dose cytarabine (phase B) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 20 publications
(31 reference statements)
6
19
0
1
Order By: Relevance
“…Given that BL is CD20-positive, and extrapolating from the clear benefit of rituximab in DLBCL [Coiffier et al 2002;Pfreundschuh et al 2006], it is reasonable to hypothesize that rituximab might improve outcomes in BL. However, the existing literature is unclear in this regard, with three retrospective studies showing no significant improvement in outcomes with the addition of rituximab to doseintense regimens [Barnes et al 2011;Todeschini et al 2012;Wästerlid et al 2011] and one study showing a clear improvement in response rates, EFS and OS with rituximab among clinical trial CR, complete response; EFS, event-free survival; PFS, progression-free survival; OS, overall survival; HR, hazard ratio; NR, not reported; NS, not significant; BL, Burkitt lymphoma; B-ALL, acute lymphoblastic lymphoma; BLL, Burkitt-like lymphoma (B-cell lymphoma, unclassifiable, with features intermediate between diffuse large B-cell lymphoma and BL); DLBCL, diffuse large B-cell lymphoma with > 95% proliferation index); HyperCVAD, hyperfractionated cyclophosphamide, vincristine doxorubicin, and dexamethasone alternating with cycles of methotrexate and cytarabine; R-HyperCVAD, rituximab + HyperCVAD; R-HyperCVAD, rituximab + hyperfractionated cyclophosphamide, vincristine, doxorubicin, and dexamethasone); CODOX-M/IVAC, cyclophosphamide, vincristine, doxorubicin, methotrexate, ifosfamide, etoposide, ara-C; COPADM, cyclophosphamide, vincristine, prednisone, adriamycin, high-dose methotrexate; R-CODOX (Rituximab+CODOX); CHOEP, cyclophosphamide, doxorubicin, vincristine etoposide, prednisone; R-CHOP, rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that BL is CD20-positive, and extrapolating from the clear benefit of rituximab in DLBCL [Coiffier et al 2002;Pfreundschuh et al 2006], it is reasonable to hypothesize that rituximab might improve outcomes in BL. However, the existing literature is unclear in this regard, with three retrospective studies showing no significant improvement in outcomes with the addition of rituximab to doseintense regimens [Barnes et al 2011;Todeschini et al 2012;Wästerlid et al 2011] and one study showing a clear improvement in response rates, EFS and OS with rituximab among clinical trial CR, complete response; EFS, event-free survival; PFS, progression-free survival; OS, overall survival; HR, hazard ratio; NR, not reported; NS, not significant; BL, Burkitt lymphoma; B-ALL, acute lymphoblastic lymphoma; BLL, Burkitt-like lymphoma (B-cell lymphoma, unclassifiable, with features intermediate between diffuse large B-cell lymphoma and BL); DLBCL, diffuse large B-cell lymphoma with > 95% proliferation index); HyperCVAD, hyperfractionated cyclophosphamide, vincristine doxorubicin, and dexamethasone alternating with cycles of methotrexate and cytarabine; R-HyperCVAD, rituximab + HyperCVAD; R-HyperCVAD, rituximab + hyperfractionated cyclophosphamide, vincristine, doxorubicin, and dexamethasone); CODOX-M/IVAC, cyclophosphamide, vincristine, doxorubicin, methotrexate, ifosfamide, etoposide, ara-C; COPADM, cyclophosphamide, vincristine, prednisone, adriamycin, high-dose methotrexate; R-CODOX (Rituximab+CODOX); CHOEP, cyclophosphamide, doxorubicin, vincristine etoposide, prednisone; R-CHOP, rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone.…”
Section: Discussionmentioning
confidence: 99%
“…High-intensity, brief duration regimens yield CR rates of 70-90%, and long-term event-free survival (EFS) rates between 45% and 97% [Evens et al 2013;Barnes et al 2011;Dunleavy et al 2011;Fayad et al 2007; Thomas et al 1999Thomas et al , 2006Rizzieri et al 2004;Mead et al 2002]. In contrast to other B-cell lymphomas, the impact of rituximab in combination with chemotherapy in BL is unclear, with some studies finding no benefit and others strongly Therapeutic Advances in Hematology 5 (1) suggestive of benefit [Wästerlid et al 2011[Wästerlid et al , 2013Todeschini et al 2012;Barnes et al 2011;Thomas et al 2006]. One randomized trial, presented in abstract form, reported an overall survival (OS) benefit of the addition rituximab to intensive chemotherapy [Ribrag et al 2012].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] More recent series and clinical trials report success rates in excess of 90% in pediatric 4,5 and 80% in adult populations. [6][7][8][9] The anti-CD20 monoclonal antibody rituximab has transformed the management of other mature B-cell malignancies. Because BL cells express abundant surface CD20, rituximab has been incorporated in multiple recent regimens reporting high success rates.…”
Section: Introductionmentioning
confidence: 99%
“…BL patients who received aggressive short-term chemotherapy demonstrated better overall survival rate than those who received chemotherapy with cyclophosphamide, doxorubicin, vincristine and prednisolone (also known as CHOP), which is routinely administered to patients with non-Hodgkin's lymphoma (23). Prophylactic cranial irradiation and prolonged maintenance have not demonstrated any proven benefits and are not currently recommended for treatment of the disease.…”
Section: Discussionmentioning
confidence: 99%